Dermatology diseases and therapy - Levine, Norman 1945 March 18- (Cambridge University Press, 2007)
Dermatology: Diseases and Treatment provides the busy clinician with an organized, condensed and practical approach to the patient with a skin problem. It includes the elements of diagnosis for hundreds of the most common cutaneous problems and provides recommendations for the management of these conditions. Also included are detailed descriptions of the most commonly used medications in dermatology today.